2013
DOI: 10.1103/physrevb.88.195407
|View full text |Cite
|
Sign up to set email alerts
|

Spin chaos manifestation in a driven quantum billiard with spin-orbit coupling

Abstract: The coupling of orbital and spin degrees of freedom is the source of many interesting phenomena. Here, we study the electron dynamics in a quantum billiard driven by a periodic electric field-a mesoscopic rectangular quantum dot-with spin-orbit coupling. We find that the spatial and temporal profiles of the observables demonstrate the transition to chaotic dynamics with qualitative modifications of the power spectra and patterns of probability and spin density. The time dependence of the wavefunctions and spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In these studies the non-Poissonian level statistics has been found which indicates the presence of quantum chaos. In our recent paper [21] we have found the development of strongly irregular dynamics in this system under the periodic driving by the electric field, which manifested itself in both charge and spin channels. Such nontrivial spin-dependent evolution of quantum states should also develop in the driving dynamics of electrons on the surface of 3D TIs and at the edge of 2D TIs, where the Dirac-Weyl Hamiltonian can be described as the limiting case of the electron Hamiltonian with extremely high linear-in-k SOC.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…In these studies the non-Poissonian level statistics has been found which indicates the presence of quantum chaos. In our recent paper [21] we have found the development of strongly irregular dynamics in this system under the periodic driving by the electric field, which manifested itself in both charge and spin channels. Such nontrivial spin-dependent evolution of quantum states should also develop in the driving dynamics of electrons on the surface of 3D TIs and at the edge of 2D TIs, where the Dirac-Weyl Hamiltonian can be described as the limiting case of the electron Hamiltonian with extremely high linear-in-k SOC.…”
Section: Introductionmentioning
confidence: 77%
“…For our set of parameters (20), (21) one can easily check that for the driving frequency ω 0 = 0.58 · 10 12 s −1 considered below the amplitude of the driving field as low as E 0 ≈ 1 V/cm may put our system into an area of instability in the Ince-Strutt diagram. When this or higher electric field is driving the dynamics, one may expect the development of irregular regimes of spin and coordinate dynamics which are coupled through the system (14a)-(14e).…”
Section: Quasiclassical Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis presented in that paper can be carried out for our system as well and we assume that the correspondence between classical and quantum chaotic behaviour holds in our case as well. A very interesting recent study of quantum billiard with spin-orbit coupling [54] provides further evidence that chaos will arise for spin-orbit coupled systems in …”
Section: B Nearest Neighbor Distributionsmentioning
confidence: 99%